Urgensi Penyaluran Bakat Anak-Remaja dalam Menghafal Al-Quran di Desa Jati Kesuma - Selamat Pohan; Armanusah Fazira Sudarmanyah (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
Character Planting is very important. In Islam character is needed as an ideal goal. One form of children's character is related to talent. A place to channel talent is needed. Why is it needed? The answer is because of the lack of talent of young people to memorize the Al-Quran, so that it becomes a problem. It should be noted that in the observations, the team found problems in the field, among these problems, namely the lack of talent for young people to memorize the Koran. For this reason, volunteers or facilitators are needed as a forum for channeling talents for Teenagers who have the potential to memorize the Al-Quran. The purpose of this activity is so that teenagers their age are not busy with their gadgets, but they are able to fill their time with positive things related to the Koran. For this reason, cadres are needed who have the talent to memorize the Al-Quran and at the same time preserve successor cadres for the realization of a civilized and Quranic society. The method used in this activity is to provide an understanding of the needs and obligations in religion, provide education on tahsin and recitation of the Al-Quran, introduce reading and writing Iqra' for beginners, and guide Tahfidz Quran for Teenagers who have the potential to become memorizers. Quran. The focus of this article is to serve as a forum for channeling the talents of Teenagers in education and religion, as a more productive diversion of time. The results of the implementation of this program, namely, Teenagers who start to Love the Koran and Recite the Al-Quran, Parents begin to realize the Urgency of Teenagers and the need to memorize the Al-Quran. This has become the focus of attention of the Community, Village Leaders and Apparatus to facilitate and contribute and accommodate. Local Teenagers' interactions with Gadgets are more controlled, with a guide. Local Youth can display their talents to the fullest. At the same time it can divert from activities that are less useful, and from here you can see the candidates who are the seeds of talent for memorizing Al-Quran cadres in the Jati Kesuma Village community.